Transformasi Guru sebagai Fasilitator Pembelajaran di Era Digital - Afriani, Gusma; Soegiarto, Ita; Suyuti, Suyuti; Amarullah, Ahmad; Aristanto, Aristanto (Civiliza Publishing, Indonesia., 2024)
The development of information and communication technology (ICT) has changed the educational landscape, encouraging the transformation of the role of teachers into learning facilitators in the digital era. This research aims to explore this transformation phenomenon by exploring shifts in learning paradigms, identifying challenges faced by teachers, evaluating strategies for solving them, and analyzing their impact on student learning. The research method used is a qualitative approach, by collecting data, including in-depth interviews with teachers who actively use technology in learning and direct observation in classes that apply a technology-based approach. The research results show that the transformation of the teacher's role involves a shift in focus from a teacher-centered learning model to a more student-oriented approach, where the teacher acts as a learning facilitator who encourages active student involvement and collaboration. Challenges such as lack of digital skills and gaps in technology access among students are major barriers to adopting these new roles. However, resolution strategies such as training and professional development, collaboration with colleagues, and differentiation of learning have proven effective in overcoming these challenges. The impacts of this transformation include increased student engagement, creativity, critical thinking, and collaboration in digital learning. In conclusion, the transformation of teachers as learning facilitators in the digital era is a complex process that requires in-depth understanding, appropriate strategies, and ongoing support to achieve optimal learning outcomes in an ever-evolving context.